Rewired signaling network in T cells expressing the chimeric antigen receptor (CAR). (9th July 2020) - Dong, Rui; Libby, Kendra A; Blaeschke, Franziska; Fuchs, Walker; Marson, Alexander; Vale, Ronald D; Su, Xiaolei
Abstract: The chimeric antigen receptor (CAR) directs T cells to target and kill specific cancer cells. Despite the success of CAR T therapy in clinics, the intracellular signaling pathways that lead to CAR T cell activation remain unclear. Using CD19 CAR as a model, we report that, similar to the endogenous T cell receptor (TCR), antigen engagement triggers the formation of CAR microclusters that transduce downstream signaling. However, CAR microclusters do not coalesce into a stable central supramolecular activation cluster (cSMAC). Moreover, LAT, an essential scaffold protein for TCR signaling, is not required for microcluster formation, immunological synapse formation, nor actin remodeling following CAR activation. However, CAR T cells still require LAT for an optimal production of the cytokine IL‐2. Together, these data show that CAR T cells can bypass LAT for a subset of downstream signaling outputs, thus revealing a rewired signaling pathway as compared to native T cells. Synopsis: The chimeric antigen receptor (CAR) triggers a rewired signaling pathway to activate T cells as compared to the T cell receptor (TCR). CAR T cells form unstable immunological synapses. LAT is not required for CAR microcluster formation. CAR activates the Gads‐SLP76‐actin pathway independently of LAT. LAT promotes but is not required for CAR‐induced IL‐2 production. Abstract : Comparison of signaling pathways employed by endogenous T‐cell receptors (TCR) and by chimeric antigen receptors (CAR) used in anti‐cancer therapy surprisingly finds the essential intracellular TCR scaffold protein LAT to be dispensable for the latter.